The Impact of Work Culture, Service, and Employee Competence on Satisfaction with E-Government Systems as Intervening Variables - Fitriadi, Ahmad Rizqi Arief; Herlambang, Toni; Sanosra, Abadi; Nursaid; Qomariah, Nurul; Ridwan, Wachid (Yayasan Sinergi Kawula Muda, 2025)
This study aims to test and analyze the role of work culture, employee service and competence on service satisfaction with the intervening variable of SPBE implementation in Jember Regency Government. This study uses a quantitative method with the Structural Equation Modeling approach with Partial Least Squares (SEM-PLS) with a population of 8,454 and involving 140 respondents. This study resulted in work culture having a positive influence on service satisfaction. The competence possessed by employees has not been able to provide a good influence on service satisfaction. While on the other hand, the work culture applied, the services provided and employee competence can make SPBE even better. The Electronic-Based Government System (SPBE) has an influence on service satisfaction. The work culture applied has no influence on service satisfaction with SPBE as an intervening variable. While the service and employee competence variables can provide an increase in SPBE service satisfaction as an intervening variable.